Language Use, Attitudes, and Women's Rights in Abortion Discourse : A Qualitative and Comparative Study on Left and Right Winged British Newspaper Articles on Abortion - Mäki, Eva-Lydia (My University, 2023)
This thesis is a critical discourse study on abortion discourse in British left and right leaning newspaper articles. This study examines the language use, attitudes, and women’s rights in the articles, and compares the differences between the articles from the more left leaning and right leaning newspapers. The data consists of ten articles from six different British newspapers: The Guardian, The Daily Record, The Daily Mirror, The Telegraph, The Daily Mail, and The Sun. This study aims at examining the word choices, attitudes, opinions, present voices, and whether women’s rights are supported or violated in abortion discourse. The theories and methods draw from Norman Fairclough’s three-dimensional framework of discourse, social theory, and Michelle Lazar’s feminist critical discourse analysis. The analysis focuses on the agencies of the writers of the articles. Those agencies include: specific word choices and whether they are positive, negative, or neutral; intertextuality, that is, quotations from other people’s voices involved in the articles; ideologies, that are the people’s attitudes and opinions present in the articles towards abortion or abortion legislation and politics; and engagement. The results showed that, in fact, there were no noteworthy differences to be found in the language use, attitudes, or views towards women’s rights between the more left leaning or right leaning newspaper articles. Thus, the hypothesis was proven to be false. However, an aspect in which there was a certain difference to be found, was between those articles where the writers’ voices were more neutral and subtle, versus these where they were more visible and opinionated. The first group used more quotations and other people’s voices, whereas the latter group had less of these. Otherwise, the two groups, that is, left and right leaning articles, did not have any major differences in any of the features that were looked at. Even though the hypothesis of this study was proven to be false, the topic of this study, that is, abortion and women’s rights, has been relevant to examine. Earlier similar studies have revealed that negative media presentation on the topic of abortion has affected negatively on the formation of people’s opinions and views towards abortion. Media presentation has also affected the general ideologies in the society, too.
Keywords: critical discourse analysis, feminist critical discourse analysis, social theory of discourse, abortion, women’s rights, abortion discourse, newspaper articles